ANALISIS PRAGMATIK PADA FUNGSI TINDAK TUTUR DALAM FILM KARYA WALT DISNEY - Widayanti, Sukasih Ratna; Kustinah, Kustinah (PRASASTI: Journal of Linguistics, 2019)
Film is one communication media to deliver message. This study investigates speech act in the film by using pragmatics approarch. Children film is chosen since children indirectly get new vocabulary in the form of word, phrase, or sentence through film. This study is entitled ‘A Pragmatic Study on the Function of Speech Act in Disney Princess Film’. It covers one important thing, such as the function of speech act in children film. This is descriptive qualitative study which reveals the data collection on the film transcript through the character’s dialogue in the film. The result of this study are as follow. The function of speech act in the children film are a) representative speech act is used to stating, insisting, reporting, summarizing, describing, proposing, and confronting; b) expressive speech act is used to asking apologize, praising, regretting, showing like or love, and showing fear; c) commisive speech act is used to promising, offering, and rejecting; and d) directive speech act is used to commanding, ordering, requesting, asking, and forcing. This result shows the function of speech act which is used in children film. Those speech act is usually imitated and restated by the children who watch movie in their daily life.